Increasing the Accuracy of Determining Activity-Based Services Tariffs for Central Surgical Installation (Case at the BLUD Hospital in Indonesia): english - Najamuddin , Yunan; Urumsah, Dekar; Mahmudi, Mahmudi; Yendrawati, Reni; Dirgahayu, Teduh; Dwi Rugiarti, Novi; Dwi Ariyani, Asri; Dewi Nindiasari, Avininda; Rosita, Rosita (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
This research aims to determine the application of cost accounting (unit cost) through the Activity-Based Costing (ABC) method in establishing service rates at Regional Public Service Agency Hospitals (BLUD Hospital). Among the unit costs studied at the BLUD Hospital, the focus was on the surgical service unit. Despite its potential, the ABC method is still underutilized for calculating unit service costs in BLUD hospitals. The evaluation compared traditional tariff calculations, based on Minister of Finance Regulation No. 3 of 2023, with calculations derived from the ABC method. The study's findings revealed that activity-based surgical service units incur unit costs of Rp. 1,205,171.55 for special surgeries, Rp. 935,780.27 for major surgeries, and Rp. 510,425.60 and Rp. 283,569.78 for medium and small operations, respectively. These unit costs serve as the foundation for determining rates by adding the direct costs of each unit. In accordance, service rates will be generated. Notably, the determined tariffs in INA-CBGs are IDR 4,250,000 for special surgeries, IDR 3,300,000 for major surgeries, IDR 1,800,000 for medium surgeries, and IDR 1,000,000 for small surgeries. Consequently, this study recommends the BLUD Hospital management to adopt the ABC method in calculating unit costs as it revealed that the costs attributed to patients in the surgical service unit were lower than the traditional costing method.